1991
DOI: 10.1080/08927019109378221
|View full text |Cite
|
Sign up to set email alerts
|

The use of block copolymers to inhibit bacterial adhesion and biofilm formation on hydrophobic surfaces in marine habitats

Abstract: Inhibition of adhesion of marine bacterial cultures to polystyrene surfaces treated with tri-block copolymers of polyethylene oxide and polypropylene oxide ('Synperonic' PE series) ranged from 21 to 100% depending on the properties of the copolymer and of the test organism. After 4 h submergence in natural marine habitats, copolymer treatment resulted in 70-100% reduction in colonisation. After 5d, the inhibitory activity was maintained in terms of colonisation by bacterial aggregates and eukaryotes, but singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…These surfactants showed an excellent short-term effectiveness, whereas in long-term tests the effect was poor. This was explained by leaching of the surfactant, abrasion by sand, interference with natural polymers, the existence of specific bacterial populations able to overcome the copolymer barrier, and biodegradation of the surfactant (18).…”
Section: Immobilized On Surfacesmentioning
confidence: 99%
“…These surfactants showed an excellent short-term effectiveness, whereas in long-term tests the effect was poor. This was explained by leaching of the surfactant, abrasion by sand, interference with natural polymers, the existence of specific bacterial populations able to overcome the copolymer barrier, and biodegradation of the surfactant (18).…”
Section: Immobilized On Surfacesmentioning
confidence: 99%
“…Poly(ethylene glycol) (PEG), also referred to as poly(ethylene oxide), has been explored as foulingresistant material [2][3][4]. Investigators have found that bacteria do not attach well to surfaces composed of PEG-modified polymers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ethylene glycol) (PEG), also referred to as poly(ethylene oxide), has been explored as foulingresistant material [2][3][4]. Investigators have found that bacteria do not attach well to surfaces composed of PEG-modified polymers [3,4]. Due to the method of preparation of the surfaces used in these initial studies, however, chemical homogeneity of the PEG exposed at the interface often could not be assured, thus the specific contribution of the PEG to the fouling-resistant properties could not be adequately assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial attachment can be considerably reduced by long-chain polymers adsorbed to surfaces, such as proteins (Fletcher & Marshall, 1982) and block copolymers (Blainey & Marshall, 1991) or alkanethiol SAMs (Ista et al, 1996) containing polyethylene oxide. Chain length and flexibility of the polymers are presumably important variables determining such effects.…”
Section: Discussionmentioning
confidence: 99%